2019
DOI: 10.1111/tpj.14159
|View full text |Cite
|
Sign up to set email alerts
|

De novo genome assembly of the stress tolerant forest species Casuarina equisetifolia provides insight into secondary growth

Abstract: These authors contributed equally to this work. SUMMARYCasuarina equisetifolia (C. equisetifolia), a conifer-like angiosperm with resistance to typhoon and stress tolerance, is mainly cultivated in the coastal areas of Australasia. C. equisetifolia, making it a valuable model to study secondary growth associated genes and stress-tolerance traits. However, the genome sequence is unavailable and therefore wood-associated growth rate and stress resistance at the molecular level is largely unexplored. We therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 74 publications
0
30
0
Order By: Relevance
“…More recently, since the introduction of high-throughput sequencing technologies, the number of genome sequencing projects has increased at an exponential rate, leading to genome assemblies for organisms previously considered too low a priority to be sequenced. For instance, high-quality genome assemblies have been released for Potentilla micrantha (Buti et al, 2017), Salvia splendens (Dong et al, 2018), Cuscuta campestris (Vogel et al, 2018) and Casuarina equisetifolia (Ye et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, since the introduction of high-throughput sequencing technologies, the number of genome sequencing projects has increased at an exponential rate, leading to genome assemblies for organisms previously considered too low a priority to be sequenced. For instance, high-quality genome assemblies have been released for Potentilla micrantha (Buti et al, 2017), Salvia splendens (Dong et al, 2018), Cuscuta campestris (Vogel et al, 2018) and Casuarina equisetifolia (Ye et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our genome-wide analysis of fig has identified the majority of eukaryotic species conserved motifs and one species-specific motif, ANHGA. For those 6mA sites of which it was not possible to infer a defined motif, we retrieved some conserved motifs: GAGG, that is present in both plants and animals (Wu et al, 2016), ACCT, already identified in Arabidopsis (Liang et al, 2018), and CAAG, found in Casuarina equisetifolia (Ye et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMRT can detect every DNA modification at single base resolution ( Zhu et al, 2018 ). Recently, 6mA has been detected on genome-wide level in eudicot model Arabidopsis thaliana ( Liang et al, 2018b ) and monocot model rice ( Oryza sativa ) ( Zhang et al, 2018 ; Zhou et al, 2018 ), as well as in non-model plants Casuarina equisetifolia ( Ye et al, 2019 ), woodland strawberry ( Fragaria vesca ) ( Xie et al, 2020 ), and soyabeans ( Glycine max) ( Yuan et al, 2020 ), and fig ( Ficus carica ) ( Usai et al, 2021 ). While combined SMRT sequencing and 6mA-IP-Seq have been used to detect genome wide 6mA levels in Arabidopsis and rice ( Liang et al, 2018b ; Zhang et al, 2018 ; Zhou et al, 2018 ), and they reveals more efficient information for dynamic distribution and pattern of 6mA compared to these 6mA studies in non-model plants.…”
Section: Ma Detection Methods In Plantsmentioning
confidence: 99%
“…Scanning electron microscope (Model TM3030Plus Tabletop microscope, Hitachi, Japan) was used to visualize the leaf surfaces of the 1.5 y forest trees, corresponding to samples in light response photosynthesis curve. Free-hand transverse sections from random branches and were stained with phloroglucinol-HCl (1% (weight/volume) phloroglucinol in 6 mol/l HCl) for 5 min for lignin visualization (Ye et al 2019;Zhang et al 2018) using stereomicroscope (Leica M205FA, Germany).…”
Section: Microscopic Observationsmentioning
confidence: 99%